Mr. Simson's knotty case : divinity, politics, and due process in early eighteenth-century Scotland - Skoczylas, Anne, 1938- (McGill-Queen's studies in the history of ideas, 2001)
The issues involved in these trials included the right of universities to discipline their professors, the degree of political control over the appointment and methodology of teachers, the preservation of factional advantage through such appointments, and the nature of the relationship between a state church and the public institutions responsible for educating its clergy. Skoczylas shows that the effect of the Enlightenment on Scottish Calvinism, which required adaptation to new developments in theology and pedagogy, was an important sub-text to the trials: the compromise reached at the end of the second led indirectly to the first secession of ultra-orthodox ministers from the Church of Scotland. More significantly, the Church became increasingly open to innovative thought so that enlightened ministers of the latter half of the century could debate matters forbidden to Simson. Mr Simson's Knotty Case breaks new ground, offering the first analysis of many ecclesiastical and political sources. Skoczylas shows that although Simson was in many ways a conservative man, despite his innovative pedagogy, the liberalizing effects of his cases thrust Scotland from the obscurity of Covenanting orthodoxy into the clarity of the Enlightenment.